2018
DOI: 10.3389/fmicb.2018.01131
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Growth and Activities of the Dominant Functional Microbiota of Chicken Manure Composts in the Presence of Maize Straw

Abstract: As a consequence of intensive feeding, the bulk deposition of livestock manure causes severe environmental problems. Composting is a promising method for waste disposal, and the fermentation process is driven by microbial communities. However, chicken manure contains diverse gut microbes, mainly species derived from Proteobacteria, which may include pathogens that threaten human health. To evaluate composting as a harmless treatment of livestock manure, the dynamics of the microbiota in two chicken manure comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 49 publications
4
18
0
2
Order By: Relevance
“…Historically, composting has been used to recycle agricultural wastes and return the composted organic matter into the soil to maintain soil fertility and crop productivity with minimum application of synthetic chemical fertilizers [ 9 ]. During composting, the diversity and structure of microbial communities, as well as chemical and physical properties of the composting substrates change dramatically in the course of several weeks [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, composting has been used to recycle agricultural wastes and return the composted organic matter into the soil to maintain soil fertility and crop productivity with minimum application of synthetic chemical fertilizers [ 9 ]. During composting, the diversity and structure of microbial communities, as well as chemical and physical properties of the composting substrates change dramatically in the course of several weeks [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [14,70] have confirmed that T. fusca is the dominant cellulose-degrading bacterium in lignocellulose compost. It has been reported that the abundance of P. fulgidum was only 3% in pure chicken manure compost, but it increased to 41% in chicken manure and straw mixed compost [71]. These results suggested that P. fulgidum can grow in high-nitrogen substrates such as SMS and chicken manure, and that the presence of both lignocellulose and nitrogen sources can significantly promote bacterial growth.…”
Section: Metaproteome Analysis Of the Dominant Microbial Communitiesmentioning
confidence: 87%
“…Lentibacillus has a close genetic relationship with Bacillus. Some of the Lentibacillus genus are dominant degraders with active amino acid metabolism, and secrete a diverse array of proteases, as revealed in metaproteomics data (34). Proteases in Daqu were shown to play a significant role in the formation of aroma components in liquor (35).…”
Section: Discussionmentioning
confidence: 99%
“…While Kroppenstedtia , Saccharopolyspora and Lentibacillus adapted to the high temperature environment and then accumulated during the last two periods. Due to the predominant presence and metabolic activity of the three bacterial genera above , the formation and accumulation of aroma substances in Daqu was made possible. It is noteworthy that the difference between the microbial composition of sesame Daqu and other flavour liquors, was that Kroppenstedtia , Saccharopolyspora and Lentibacillus, were predominant in the sesame flavour liquors and may play an important microecological role in the formation of the roasted sesame and floral aromas.…”
Section: Discussionmentioning
confidence: 99%